Viscoelastic Dynamic Response of Asphalt Pavement in Long Slope Sections - Gao, Yuanyuan; Dong, Shuai; Xiao, Han; Hlupo, Nkosilathi lovewell; Liu, Zhi (Periodica Polytechnica Civil Engineering, 2023)
To deeply understand the performance of asphalt pavement in long slope sections, the object of this paper is to obtain the viscoelastic dynamic response of asphalt pavement in long slope sections considering interface bonding conditions. An asphalt pavement model is built, and then for solving the problem, the Laplace-Hankel transformation is used to transfer the partial differential equations to the ordinary differential equations. Transfer matrices are adopted to present the relationship of stress and displacement between the pavement surface and any pavement depth, and a special transfer matrix characterizes the interface bonding condition. By this method, the analytical solution of the stress and displacement at any pavement position is received. After that, an example of asphalt pavement in a long slope section is introduced considering the distribution of stress and displacement, the magnitude of the horizontal load, and the interface bonding strength. The horizontal vehicle load affects the distribution of shear stress τrz in the pavement. The interface bonding strength is more important in long slope sections than in any other normal section of asphalt pavement.